Analisis Sistem Pengendaalian Internal Siklus Penjualan Pada CV. Nirwana Offset Surabaya. - Deborah, Deborah; Paramitha, Melvie (Jurnal Etnik: Ekonomi-Teknik, 2022)
Internal control in the company is one of the things that important in sales procedures to be able to achieve company goals. CV. Nirwana Offset is engaged in the printing sector which has been established since 2007. The purpose of this study is to analyze the sales cycle internal control system using COSO. Where COSO has five components, namely the control environment, risk assessment, information and communication control activities, and supervision. This research was conducted with a descriptive method with a qualitative approach. Data collection techniques were carried out by interview, observation and documentation. The data sources used are primary data sources or get data directly from the company. The results of research on CV. Nirwana Offset shows that internal control is not yet fully effective and in accordance with COSO components. because there are still some components that still have weaknesses. Namely components of risk assessment, control and supervision activities that still have weaknesses against inadequate sales documents, the company still does not have billing letters, offer letters and receipts. The company still uses manual sales notes and does not write sales notes directly. lack of supervision of the inventory of mold raw materials and lack of supervision on the molding machine. With the existing weaknesses, the sales cycle will not run effectively and efficiently due to a lack of internal control.